(untitled) (Economic studies journal, 2020)
The study aimed to highlight the role of entrepreneurship in society and its role in promoting social responsibility, and provide a conceptual framing of the concepts of entrepreneurship and social responsibility, and identify the nature of the relationship between the dimensions of entrepreneurship and social responsibility dimensions, and study the most important obstacles to entrepreneurship at Zawia University. The problem of the study was as follows: Is there a role for entrepreneurship in its dimensions (creativity, risk, initiative, innovation) in promoting social responsibility dimensions (moral responsibility, legal responsibility, economic responsibility, human responsibility) at the university. The main hypothesis of the study was formulated: There is no statistically significant impact of the dimensions of entrepreneurship (creativity, risk, initiative, innovation) in promoting social responsibility in its dimensions (moral responsibility, legal responsibility, economic responsibility, human responsibility) at the university. A questionnaire was designed to collect data on the field side and was distributed to a purposive sample of the deans of faculties and directors of departments in the general administration of the university. The statistical program (SPSS) was used to process the data and the study reached a number of results, the most important of which is the presence of a significant effect of entrepreneurship on social responsibility and the value of regression coefficient (0.651). Promoting social responsibility of the university.